A novel method of guideline development for the diagnosis and management of mild to moderate hypertension. - Adams, J L (1999)
BACKGROUND: There are large numbers of clinical guidelines available covering many clinical areas. However, the variable quality of their content has meant that doctors may have been offered advice that has been poorly researched or is of a conflicting nature. It has been shown that local involvement in guideline development increases the likelihood of their use. AIM: To develop a guideline to be used by general practitioners in six practices in Birmingham from existing evidence-based guidelines. METHOD: Recommendations from the four most cited international hypertension guidelines, and the more recently published New Zealand guidelines, were divided into subject areas and tabulated to facilitate direct comparison. Where there was complete or majority (> or = 3/5) agreement, the recommendation was taken as acceptable for inclusion in the new guideline. Where there was disagreement (< or = 2/5), recommendations were based on the best available evidence following a further MEDLINE literature search and critical appraisal of the relevant literature. Each recommendation was accompanied by a grade of evidence (A-D), as defined by the Canadian Hypertension Society, and an 'action required' statement of either 'must', 'should', or 'could', based on the Eli-Lilly National Clinical Audit Centre Hypertension Audit criteria. The recommendations were summarized into a guideline algorithm and a supporting document. The final format of both parts of the guideline was decided after consultation with the practice teams. The practices individually decided on methods of data collection. RESULTS: The guideline was presented as a double-sided, A4 laminated sheet and an A4 bound supporting document containing a synthesis of the original guidelines in tabular form, a table of the resulting recommendations, and appendices of current literature reviews on areas of disagreement. The content of the final Birmingham Clinical Effectiveness Group (BCEG) guideline differed minimally from any of the original guidelines. CONCLUSION: The main strength of this method of guideline development may lie, not in the actual content of the resulting guideline, but in the strength of ownership felt by the BCEG and the practices following its development. While the full process is unlikely to be possible for general practitioners working outside an academic environment, the techniques used could provide a framework for practitioners to adapt national and international guidelines for use at a local level.